Design and Implementation on Efficient Display Algorithm of Embedded GIS Map - Zhao Yu-Feng; Zeng Jun (2012 International Conference on Industrial Control and Electronics Engineering, 2012)
Embedded GIS map display technology based on QR-tree spatial index algorithm is described combining the characteristics of embedded technology and GIS technology. The shortage of QR-tree algorithm is analyzed and improved algorithm is put forward in paper. The method of space index to improve data retrieval speed is proposed using the improved QR-tree. Rapid display of embedded GIS system map in Windows mobile 6 simulator is realized and the simulation result shows the algorithm is effective.